2021
DOI: 10.1007/s00438-020-01759-6
|View full text |Cite
|
Sign up to set email alerts
|

Total flavonoids of Radix Tetrastigma suppress inflammation-related hepatocellular carcinoma cell metastasis

Abstract: This study aimed to investigate the effects of the total flavonoids of Radix Tetrastigma (RTF) on inflammation-related hepatocellular carcinoma (HCC) development. Extracted RTF was diluted to different concentrations for subsequent experiments. HCC cells were cotreated with lipopolysaccharide (LPS) and RTF to investigate the effects of RTF on LPS-stimulated HCC cells. A CCK-8 kit was used to measure cell proliferation. Apoptosis was detected with a flow cytometer. Cell migration and invasion were quantified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In detail, in vitro evidence from HepG2 and SMMC7721 cells has indicated that the activation of mitogenactivated protein kinase kinase 4 (MKK4)/JNK signaling [62] potentiates metastasis, while the combination of in vitro and in vivo evidence from HepG2, Hep3B, and SMMC7721 cell lines implicated the downregulation of NF-κB, resulting in a decrease in TNFα and IL-6 expression with the inhibition of metastasis [61]. The latter was also validated by Liu et al, who further introduced the flavonoids of Radix Tetrastigma, which share NF-κB inhibiting properties, as promising chemotherapeutic regimens to target metastases [63]. A second pro-metastatic mechanism is the formation of NETs [64,65].…”
Section: Tlr4 Signaling In Hcc Metastasismentioning
confidence: 88%
See 1 more Smart Citation
“…In detail, in vitro evidence from HepG2 and SMMC7721 cells has indicated that the activation of mitogenactivated protein kinase kinase 4 (MKK4)/JNK signaling [62] potentiates metastasis, while the combination of in vitro and in vivo evidence from HepG2, Hep3B, and SMMC7721 cell lines implicated the downregulation of NF-κB, resulting in a decrease in TNFα and IL-6 expression with the inhibition of metastasis [61]. The latter was also validated by Liu et al, who further introduced the flavonoids of Radix Tetrastigma, which share NF-κB inhibiting properties, as promising chemotherapeutic regimens to target metastases [63]. A second pro-metastatic mechanism is the formation of NETs [64,65].…”
Section: Tlr4 Signaling In Hcc Metastasismentioning
confidence: 88%
“…A growing body of evidence implicates the JAK2/STAT3 signaling axis in the progression and invasion of HCC [60]. In this direction, TLR4 signaling contributes to the metastatic capacity of HCC cells in two ways [61][62][63][64][65]. First, the stimulation of the TLR4 signaling pathway by LPS can enhance their metastatic potential either directly through MKK4/JNK and TLR4/NF-κB signaling [62], or indirectly via the upregulation of IL-6 and TNFα [66].…”
Section: Tlr4 Signaling In Hcc Metastasismentioning
confidence: 99%
“…The intracellular inflammatory responses have been highly correlated with the metastatic progression in many types of cancer 32–39 . The activation of NLRP3 inflammasome has also been shown to promote cancer metastasis 11,13,15,16,40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…30 In this study, AIM2 upregulation is dominant for LUAD derived from The intracellular inflammatory responses have been highly correlated with the metastatic progression in many types of cancer. [32][33][34][35][36][37][38][39] The activation of NLRP3 inflammasome has also been shown to promote cancer metastasis. 11,13,15,16,40,41 Nevertheless, AIM2 downregulation has been correlated with a poorer prognosis, probably due to an increased metastatic potential, in renal cell carcinoma 42 and hepatocellular carcinoma.…”
Section: Aim2 Upregulation Potentiates the Expression Of Pd-l1 In Smo...mentioning
confidence: 99%
“…For example, for stilbene synthase ( STS ) genes, most stilbene‐producing plant species (e.g., Sorghum bicolor , Arachis hypogaea ) possess small families of closely related paralogs, while the genome of grapevine contains a large family of putative STS genes (Parage et al., 2012). It is therefore possible that a unique expansion of the STS gene family contributes to the high abundance and chemical diversity of stilbenes throughout Vitaceae species and varieties (Liu et al., 2021; Suprun et al., 2020; Wang et al., 2016). Our previous phylogeographic studies have shown that T. hemsleyanum consists of two lineages in Southwest (SW) and Central‐South‐East (CSE) China (Wang et al., 2015).…”
Section: Introductionmentioning
confidence: 99%